Quantification of biomass feedstock availability to a biorefinery based on multi-crop rotation cropping systems using a GIS-based method - Martinez, Adrian; Maier, Dirk E. (My University, 2015)
The feasibility of utilizing cellulosic biomass as an energy feedstock is dominated by factors such as facility location, feedstock availability, and transportation cost. Our previous case study showed improvements in quantification of feedstock availability for a biorefinery by introducing the effect of field-level yield variance and variable residue removal rates as improvement parameters into the GIS-based analysis. Even though the improved GIS-based method enhanced quantification of feedstock availability with the addition of the improvement parameters, a biorefinery would most likely procure more than one feedstock type. In this case study, quantification of feedstock availability based on multi-crop rotation cropping systems was done using the previously improved GIS-based variable residue removal (VRR) method. We observed on average a 3,793 ±5,733 DT per service area difference when increasing the number of crops used to estimate feedstock quantification. The supplementary use of crop-specific VRR rates affected residue availability, given that a crop’s residue removal rate is influenced by crop yield, crop rotation, soil characteristics, as well as field location and management. It was also observed that the amount of available hectares of the three main crops analyzed in this case study affected residue availability. Corn represented 26.2% (440,636 ha; 1,101,591 acres), sorghum represented 12.9% (217,432 ha; 543,579 acres), and wheat represented 60.9% (1,024,607 ha; 2,561,518 acres) of the hectares in the study area. The validation study showed the importance of taking into account the seasonal availability of crop residue when estimating procurement service areas, given that in some cases feedstock requirements were not met.
Keywords: Biomass; Feedstock availability; GIS; Transportation logistics; Wind Erosion Prediction System (WEPS)